Digital existence: ontology, ethics and transcendence in digital culture - Lagerkvist, Amanda (Routledge studies in religion and digital culture, 2020)
Medial ontologies. Irremediability : on the very concept of digital ontology / Justin Clemens and Adam Nash ; Umwelt and individuation : digital signals and technical being / Jonas Andersson Schwarz ; Digital unworld(s) : the Bielefeld conspiracy / Yvette Granata -- Being human : extension, exposure and ethics. You have been tagged : magical incantations, digital incarnations and extended selves / Paul Frosh ; Surveillance, sensors, and knowledge through the machine / Sun-ha Hong ; Social media and the care of the self / Ganaele Langlois ; The ethics of digital being : vulnerability, invulnerability, and "dangerous surprises" / Vincent Miller -- Transcendence : beyond life, death and the human. The Internet is always awake : sensations, sounds and silences of the digital grave / Amanda Lagerkvist ; Digital rituals and the quest for existential security / Johanna Sumiala ; Cybernetic animism : non-nhuman personhood and the Internet / devin Proctor ; Death in life and life in death : forms and fates of the human / Connor Graham and Alfred Montoya